Brassinosteroids participate in the control of basal and acquired freezing tolerance of plants - Eremina, Marina; Unterholzner, Simon J.; Rathnayake, Ajith I.; Castellanos, Marcos; Khan, Mamoona; Kugler, Karl G.; May, Sean; Mayer, Klaus F.X.; Rozhon, Wilfried; Poppenberger, Brigitte (National Academy of Sciences, 2016)
Brassinosteroids (BRs) are growth-promoting plant hormones that play a role in abiotic stress responses, but molecular modes that enable this activity remain largely unknown. Here we show that BRs participate in the regulation of freezing tolerance. BR signaling-defective mutants of Arabidopsis thaliana were hypersensitive to freezing before and after cold acclimation. The constitutive activation of BR signaling, in contrast, enhanced freezing resistance. Evidence is provided that the BR-controlled basic helix–loop–helix transcription factor CESTA (CES) can contribute to the constitutive expression of the C-REPEAT/DEHYDRATION-RESPONSIVE ELEMENT BINDING FACTOR (CBF) transcriptional regulators that control cold responsive (COR) gene expression. In addition, CBF-independent classes of BR-regulated COR genes are identified that are regulated in a BR- and CES-dependent manner during cold acclimation. A model is presented in which BRs govern different cold-responsive transcriptional cascades through the posttranslational modification of CES and redundantly acting factors. This contributes to the basal resistance against freezing stress, but also to the further improvement of this resistance through cold acclimation.